2000
DOI: 10.1007/s001140050709
|View full text |Cite
|
Sign up to set email alerts
|

Fever in honeybee colonies

Abstract: Honeybees, Apis spp., maintain elevated temperatures inside their nests to accelerate brood development and to facilitate defense against predators. We present an additional defensive function of elevating nest temperature: honeybees generate a brood-comb fever in response to colonial infection by the heat-sensitive pathogen Ascosphaera apis. This response occurs before larvae are killed, suggesting that either honeybee workers detect the infection before symptoms are visible, or that larvae communicate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 4 publications
3
143
0
8
Order By: Relevance
“…Immune priming in Formica selysi workers following challenge with Beauveria bassiana is short term (Reber and Chapuisat, 2012) raising the possibility that colony living precludes the necessity of having a prolonged immune priming effect as other compensatory mechanisms may be operating in the colony. For example, in honey bee colonies an elevated nest temperature is generated as a colony-level response to prevent chalk brood (Starks et al, 2000). Social immunity in insects has been suggested in a number of colony based communities and it has been demonstrated that ants which are infected within a colony can regurgitate droplets which were capable of transferring immune factors to other uninfected ants (Hamilton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Immune priming in Formica selysi workers following challenge with Beauveria bassiana is short term (Reber and Chapuisat, 2012) raising the possibility that colony living precludes the necessity of having a prolonged immune priming effect as other compensatory mechanisms may be operating in the colony. For example, in honey bee colonies an elevated nest temperature is generated as a colony-level response to prevent chalk brood (Starks et al, 2000). Social immunity in insects has been suggested in a number of colony based communities and it has been demonstrated that ants which are infected within a colony can regurgitate droplets which were capable of transferring immune factors to other uninfected ants (Hamilton et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Like all animals, individual honeybees recruit physiological and immunological defence against disease agents (Evans et al, 2006;Schmid et al, 2008;Wilson-Rich et al, 2008). Moreover, as well as individual immunity, honeybees also show several physiological, behavioural and organizational colony-level adaptations such as spatial and behavioural compartmentalization of worker bees on the nest (Naug and Camazine, 2002;Naug, 2008), social fever (Starks et al, 2000), nest construction and enrichment with antimicrobial material (Simone et al, 2009;Baracchi and Turillazzi, 2010;Baracchi et al, 2011), grooming (Kolmes, 1989;Boecking and Spivak, 1999), hygienic behaviour (Rothenbuhler and Thompson, 1956;Spivak and Gilliam, 1998a,b;Richard et al, 2008), undertaking (Visscher, 1983) and self-removing (Kralj and Fuchs, 2006;Naug and Gibbs, 2009;Rueppell et al, 2010). Behaviour, in particular, plays an important role in infection control: removal, quarantine or exile of infected individuals can reduce the exposure of a population once disease takes hold (Clancy, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural fever is an important self-cure of some fungal infections thanks to which infected insects deliberately move themselves to hotter places which are detrimental to the fungus, but not to the host. It has been documented to occur in several different insect orders (flies (Diptera), locusts (Orthoptera), and honeybees (Hymenoptera)) and with examples from several groups of insect pathogens (Anderson et al, 2013;Blanford and Thomas, 2001;Kalsbeek et al, 2001;Starks al., 2000). In many cases, morphological examination of fungal structures using light microscopy is sufficient to determine the pathogen to genus level, while determination to species level may require molecular tools.…”
Section: Fungimentioning
confidence: 99%